Knowledge, attitude, and practice of surgical site infection prevention among operating room nurses in southwest China - Wen Feng; Wipa Sae-Sia; Luppana Kitrungrote (Belitung Raya Foundation, Indonesia, 2022)
Background: Surgical site infection has become a problem in the operating room, and the nurses’ knowledge, attitude, and practice could impact the incidence of the infection. Unfortunately, there is a dearth of studies on this issue in China. Therefore, determining nurses’ knowledge, attitude, and practice of surgical site infection prevention is necessary. Objectives: This study aimed to examine the knowledge, attitude, and practice of surgical site infection prevention and their relationships, as well as to identify differences in knowledge, attitude, and practice of surgical site infection prevention according to nurses’ demographic characteristics. Methods: A sample of 999 operating room nurses participated in 49 tertiary hospitals and 75 secondary hospitals in Guizhou Province, Southwest China. Data were collected using validated questionnaires through a Chinese survey website. Data were analyzed using descriptive statistics, One-Way Analysis of Variance, and Pearson product-moment correlation. Results: The knowledge of surgical site infection prevention was at a low level, the attitude was positive, and the practice was at a high level. Approximately 39% of the nurses passed knowledge scores of ≥ 70%, 60% gave a positive attitude score of ≥ 80%, and 76% achieved a practice score of ≥ 80%. The nurses’ attitude was positively related to knowledge (p < .01), and practice (p < .01), respectively. However, knowledge and practice did not significantly relate. The age group of 30-39 years old had significant higher knowledge than other age groups. The nurses with working experience of 6-15 years had significant higher knowledge scores than other groups. In addition, the nurses with one time of training frequency had significant lower attitude and practice scores than those with six to ten times of training frequency. Conclusion: Approximately 60% of operating room nurses still had inadequate knowledge regarding surgical site infection prevention, but they had a positive attitude and high level of practice. The findings of this study might serve as an input for nurse administrators or policymakers to provide updated knowledge or guideline, closed supervision, and in-service training on surgical site infection prevention for operating room nurses.